Contemporary organizational theory: The demographic, relational, and cultural perspectives. Issue 3 (15th February 2019) - Haveman, Heather A.; Wetts, Rachel
Abstract: We review three perspectives—demographic, relational, and cultural—that have dominated sociological research on organizations during the past four decades. These perspectives arose in reaction to the atomistic and rationalist–adaptationist assumptions of earlier perspectives on organizations. These perspectives have different conceptions of social structure and thus different conceptions of what creates opportunities for and constraints on action. The demographic perspective holds that social structure is constituted by distributions of social actors along salient dimensions of social and physical space; the relational perspective, by webs of social relationships; and the cultural perspective, by widely shared and patterned understandings of reality and possibility. These perspectives also have different conceptions of identity and therefore motivations for action. For demographers, identity derives from position, absolute or relative, along salient dimensions of social life; for relational scholars, from ties among individuals, groups, and organizations; and for cultural scholars, from social interaction. All three perspectives have been applied to explain behavior at five different levels of analysis: the individual, group or organizational subunit, organization, industry or organizational population, and field. Up to the 1990s, these perspectives were generally applied separately, but over the past two decades, studies have increasingly used multiple perspectives.